2013
DOI: 10.1186/1471-2318-13-13
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 deficiency and diseases in elderly people – a study in nursing homes

Abstract: BackgroundVitamin deficiency is a cause of health related problems in elderly people. The aims were to study associations between vitamin B6 (B6) and diseases (primarily functional gastrointestinal disorders) in elderly people in nursing homes, the prevalence of B6 deficiency and factors associated with B6 deficiency.MethodsThis cross-sectional study included residents in nursing homes. Demographics, nutritional status (Mini Nutritional Assessment, MNA® ), physical activity, activity of daily living (Katz Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 25 publications
3
62
0
3
Order By: Relevance
“…IL-4 production of lymphocytes in vitamin B6 deficient mice was promoted more than that in vitamin B6 normal mice, which exhibited a trend similar to that obtained by Doke et al [15]. The vitamin B6 deficiency did not change IFN- γ production, which was also described in a study by Kjeldby et al [8]. They found that vitamin B6 deficiency via the feeding of 4-deoxypyridoxine, a potent antagonist of vitamin B6 coenzyme, does not impair the production of IFN- γ in mice infected with Trichinella spiralis [8].…”
Section: Discussionsupporting
confidence: 85%
“…IL-4 production of lymphocytes in vitamin B6 deficient mice was promoted more than that in vitamin B6 normal mice, which exhibited a trend similar to that obtained by Doke et al [15]. The vitamin B6 deficiency did not change IFN- γ production, which was also described in a study by Kjeldby et al [8]. They found that vitamin B6 deficiency via the feeding of 4-deoxypyridoxine, a potent antagonist of vitamin B6 coenzyme, does not impair the production of IFN- γ in mice infected with Trichinella spiralis [8].…”
Section: Discussionsupporting
confidence: 85%
“…This includes attention to medication reconciliation, polypharmacy, and discontinuation of high-risk geriatric medications when not indicated. (43; 55) For example, antipsychotic medications initiated in the acute care setting for agitated delirium are often continued without indication and potentially increase the risk for rehospitalization. (43; 46; 56) In addition, care should be made to minimize the use of urinary catheters, peripherally inserted central catheters (PICC lines), and other indwelling devices at the time of discharge, as these present potential safety hazards and increased risk of rehospitalization.…”
Section: Interventions For Patients Discharged To Post-acute Care Facmentioning
confidence: 99%
“…(43; 46; 56) In addition, care should be made to minimize the use of urinary catheters, peripherally inserted central catheters (PICC lines), and other indwelling devices at the time of discharge, as these present potential safety hazards and increased risk of rehospitalization. (55; 57; 58) Finally, patients transitioning to PAC facilities should be included in routine advanced care planning discussions. These should provide adequate information about short- and long-term prognosis, expectations about the PAC setting, and discussion of goals of care to ensure that future healthcare decisions align with patient preferences.…”
Section: Interventions For Patients Discharged To Post-acute Care Facmentioning
confidence: 99%
“…Recent studies have suggested, however, that even an apparently adequate B-6 intake may not suffice to guarantee normal plasma levels in elderly people, probably due to its lower absorption, higher catabolism, and impaired phosphorylation. 39 Given these premises, the higher RDA adopted by the US Food and Nutrition Board and the Italian Society of Human Nutrition for older women (ie, a daily intake of 1.5 mg), could be appropriate for older women, too.…”
Section: Discussionmentioning
confidence: 99%